Performance improvement of the RSM970S radar speed controller of ASECNA, Douala International Airport - Angon, Moussa Bessike; Florence, Offolé; Séverin, Nguiya; Jordan, Moune Cédric; Max, Ndoumbé Matéké (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This article addresses the direct torque control associated with artificial intelligence for the control of the RSM970S radar of The Agency for the Safety of Air Navigation in Africa and Madagascar (ASECNA), Douala International Airport. The radar is driven by two identical induction motors powered by a single inverter. Direct torque control is associated with fuzzy logic and artificial neural networks. The test results performed in MATLAB/Simulink showed an improvement in the dynamic performance of the drive system compared to a conventional direct torque control. There is an overshoot in speed during the steady state of less than 0.955% of the neural technique over the fuzzy technique. But also, an accuracy of 99.58% of the two techniques proposed in this article. These results ensure good precision and stability of the radar in the detection of airplanes in the Cameroonian airspace.